Phylogeography of the horse mussel Modiolus modiolus - Halanych, Kenneth M.; Vodoti, E. Thuróczy; Sundberg, Per; Dahlgren, Thomas G. (Journal of the Marine Biological Association of the United Kingdom, 2013)
Phylogeographic inferences concerning marine species are largely based on intertidal species. In high latitudes, intertidal species have been affected by ice coverage and ice scour, and therefore show northern range limitations during glaciations. In this study, we use the subtidal horse mussel ( Modiolus modiolus ) to investigate whether generalizations about genetic structure of high latititude intertidal species, specifically in the North Atlantic, are representative of other near shore taxa. We analysed genetic diversity, molecular variance, and geographical patterns of genetic relatedness using data from the mtDNA CO1 gene. Although we do find little to no haplotype structure in the North Atlantic, our results show that north-eastern Pacific individuals represent a different haplotype network with no haplotypes in common with Atlantic individuals. Thus, M. modiolus in the Pacific may represent an unrecognized species. Genetic diversity and population expansion times suggest a Pacific origin is most likely, with subsequent dispersal to the Atlantic. The lack of genetic structure in the Atlantic suggests that a rapid range expansion occurred less than 50 KYA, rather than a stepping stone mode of dispersal.